The Indris Have Got Rhythm! Timing and Pitch Variation of a Primate Song Examined between Sexes and Age Classes - Gamba, Marco; Torti, Valeria; Estienne, Vittoria; Randrianarison, Rose M.; Valente, Daria; Rovara, Paolo; Bonadonna, Giovanna; Friard, Olivier; Giacoma, Cristina (Frontiers in Neuroscience, 2016)
A crucial, common feature of speech and music is that they show non-random structures over time. It is an open question which of the other species share rhythmic abilities with humans, but in most cases the lack of knowledge about their behavioural displays prevents further studies. Indris are the only lemurs who sing. They produce loud howling cries that can be heard at several kilometres, in which all members of a group usually sing. We tested whether overlapping and turn-taking during the songs followed a precise pattern by analysing the temporal structure of the individuals' contribution to the song. We found that both dominants (males and females) and non-dominants influenced the onset timing one another. We have found that the dominant male and the dominant female in a group overlapped each other more frequently than they did with the non-dominants. We then focused on the temporal and frequency structure of particular phrases occurring during the song. Our results show that males and females have dimorphic inter-onset intervals during the phrases. Moreover, median frequencies of the unit emitted in the phrases also differ between the sexes, with males showing higher frequencies when compared to females. We have not found an effect of age on the temporal and spectral structure of the phrases. These results indicate that singing in indris has a high behavioural flexibility and varies according to social and individual factors. The flexible spectral structure of the phrases given during the song may underlie perceptual abilities that are currently unknown in other nonhuman primates, such as the ability to recognize particular pitch patterns.